Western water A-to-Z : the history, nature, and culture of a vanishing resource - Crifasi, Robert. R. (University Press of Colorado, 2023)
"Western Water A-to-Z is the first field guide dedicated to Western water. Reinventing this twentieth-century genre for a twenty-first-century audience, Crifasi describes water projects, the culture of water, the ecosystems that water projects have created or destroyed, and the reliance of modern life on this critical resource"--